Ciona pomponiae Monniot & Monniot 1989 - Sanamyan, Karen; Sanamyan, Nadya (Zenodo, 2007)
Ciona pomponiae Monniot & Monniot, 1989 (Figure 1) Ciona pomponiae Monniot and Monniot, 1989: 17. Ciona gefesti Sanamyan, 1998: 98. Material examined: RV Keldish , cruise 22, st. 2328, 1814– 1920m, 53°26.59'N, 160°21.00'E – 53°25.76'N, 160°21.40'E, 14 August 1990, one specimen. Previous records: E Pacific, Galapagos Islands (Monniot and Monniot 1989); Bering Sea (Sanamyan, 1998). Description. The laterally flattened specimen is 30mm high and 12mm wide. The test is firm (in alcohol) and translucent and colourless. Several thick branched root-like processes of the test are on both sides of the posterior end of the body. It was not possible to determine how the specimen was attached, although it appears to have been attached by more than its posterior end. The body was detached from the test in preservative. Both apertures are on short obscurely lobed siphons (number of lobes cannot be counted). The branchial siphon is terminal and the atrial is in the middle of the dorsal mid-line of the body. Longitudinal muscle ribbons continue from the siphons to the posterior end of the body. On each side, three of these originate on the branchial siphon and two on the atrial. The dorsal ribbon of the branchial siphon and ventral ribbon of the atrial siphon fuse together in the middle of the body to form one muscle, so four evenly spaced longitudinal ribbons are on each side of the posterior half of the body. Transverse (circular) body muscles are thin, numerous, but well spaced, not forming a continuous layer. On the siphons they more crowded and thicker, forming definite sphincters. About 30 long curved branchial tentacles are attached to the margin of a high muscular velum. The prepharyngeal band is composed of an unusually high anterior and a low posterior lamella and is not indented dorsally. A small C-shaped dorsal tubercle is just anterior to a rather large ganglion. The neural gland is small, on the right side of the ganglion. The flat branchial sac lacks any plications. Regularly spaced lamellar transverse vessels bear longitudinally flattened, often hooked papillae. Both papillae and transverse vessels are high, and thus internal longitudinal vessels, about 30 on each side, supported by these papillae, are above the surface of the branchial sac. Tips of the papillae project out markedly beyond the longitudinal vessels. Thin parastigmatic vessels cross some (but not all) rows of stigmata. Branchial meshes are rectangular, each with about five stigmata. About 25 dorsal languets significantly increase in length from the anterior to the posterior end of the branchial sac. The endostylar appendix is absent. The retropharyngeal groove running along the posterior end of the branchial sac is narrow near the endostyle but widens significantly toward the opposite (dorsal) side (Fig. 1C). A pair of large pharyngeo-epicardiac openings is almost halfway between endostyle and oesophageal opening, somewhat closer to the latter, slightly behind the pyloric end of the stomach (Fig. 1C). The narrow primary gut loop, with short oesophagus, small globular stomach and a post-pyloric length of the intestine forms a short, narrow, horizontal loop across the left side of the posterior end of the branchial sac and the rectum extends in a straight line under the dorsal mid-line of the branchial sac. Numerous clear inner longitudinal folds are visible through the transparent stomach wall. The stomach is sharply separated from the oesophagus and the intestine. The voluminous intestine is filled with fine particles. The straight rectum ends in a clearly lobed anus. A compact ovary is in the gut loop and a C-shaped female opening is just above the anus. Male openings were not seen. Pigment spots were not detected on the genital papilla. A spherical body containing a single parasitic copepod was found in the body wall. Remarks. The original description of this species is based on one specimen collected at 300–800 m near the Galapagos Islands. Ciona gefesti Sanamyan, 1998 from the Bering Sea is certainly conspecific, Sanamyan (1998) recognized the close affinity of his species with C. pomponiae but assigned it to a new species based on the great geographical distance from the location of C. pomponiae and supported by a number of minor features, including the presence of clear stomach folds and lobed anus in C. gefesti . The present specimen, from East Kamchatka, is smaller, but in most features identical with the type specimen of C. gefesti . The only difference between North Pacific specimens and the original description of C. pomponiae is the shape of the anus, smooth in the Galapagos specimen described by Monniot and Monniot (1989) and lobed in both North Pacific specimens. However, anal lobes are not prominent and the anus may appear smooth, especially if the specimen is contracted or not in a good condition. The structure of the stomach wall also is not a reliable feature separating these specimens and although the stomach appears as almost smooth on Monniots' figure (Monniot and Monniot, 1989, Fig.1 E,G) it is described as having internal plications visible through the stomach wall as in the present specimen. The number of longitudinal muscle bands, four in the posterior half of the body, is identical in all three known specimens and may be considered a stable distinguishing feature of this species. Ciona mollis Ritter, 1907 is the only other deep-water species of this genus known from the northern Pacific. It differs from C. pomponiae in the unusual structure of the branchial sac with doubled longitudinal vessels (see Monniot, 1998), absence of transverse body muscles (reported by Ritter, 1907 and confirmed by Monniot, 1998), and several less prominent features. Monniot and Monniot (1989) proposed a relationship between C. mollis and C. gelatinosa Bonnevie, 1896, but several features distinguish these species (see C. gelatinosa below). : Published as part of Sanamyan, Karen & Sanamyan, Nadya, 2007, Poorly known Ascidiacea collected in the vicinity of the Commander Islands and East Kamchatka, NW Pacific, pp. 55-68 in Zootaxa 1579 (1) on pages 56-58, DOI: 10.11646/zootaxa.1579.1.3, http://zenodo.org/record/5097273 : {"references": ["Monniot, C. & Monniot, F. (1989) Ascidians collected around the Galapagos Islands using the Johnson-Sea-Link research submersible, Proceedings of the Biological Society of Washington, 102 (1), 14 - 32.", "Sanamyan, K. & Sanamyan, N. (1998) Some deep-water ascidians from the NW Pacific (Tunicata: Ascidiacea). Zoosystematica Rossica, 7 (2), 209 - 214.", "Ritter, W. E. (1907) The ascidians collected by the United States Fisheries Bureau steamer Albatross on the coast of California during the summer of 1904. University of California Publications in Zoology, 4, 1 - 52.", "Monniot, C. (1998) Abyssal ascidians collected from proximity of hydrothermal vents in the Pacific Ocean. Bulletin of Marine Science, 63 (3), 541 - 558", "Bonnevie, K. (1896) Ascidiae Simplices og Ascidiae Compositae fra Nordhavs Expeditionen. Norske Nordhavs Expedion, 7 (23), 1 - 16."]}